(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
We consider advection of floating passive tracer in the White Sea using a hydrodynamical model of sea circulation JASMINE. Simulations show that the Onezhskiy Bay is a hydrodynamical trap for tracers: concentration there decrease more slowly. Typical times needed to remove concentrated tracer completely from bays are estimated. General scheme of tracer advection is described.